Sin Í an Cheist a Chuireas Orm Féin: Modern Irish Presentative Constructions - Eshel, Orit (Studia Celtica Posnaniensia, 2017)
This article surveys two types of Modern Irish presentative constructions. These constructions open with a presentative element and introduce an NP (entity) or a nexus (a situation or an event involving an entity) into the discourse. I describe the constructions’ poetic functions in literary narratives by Pádraic Ó Conaire (1882-1928). The first type of presentative construction opens with one of the deictic-presentative elements seo ‘here’, sin ‘there’ or siúd ‘yonder’. The second type of presentative construction features as a presentative element of various forms of perception and cognition verbs, such as d’fheicfeá ‘you’d see’ and shílfeá ‘you’d think’. Presentative constructions in literary narrative are used in several functions: expression of a point of view, either the narrator’s or that of a character, scene-setting, explication, and signalling boundaries in the text in varying degrees of cohesion and delimitation. The latter is also used to ‘sudden effect’, adding drama and speeding up story time.